2021
DOI: 10.1073/pnas.2021893118
|View full text |Cite
|
Sign up to set email alerts
|

In situ small-angle X-ray scattering reveals solution phase discharge of Li–O 2 batteries with weakly solvating electrolytes

Abstract: Electrodepositing insulating lithium peroxide (Li2O2) is the key process during discharge of aprotic Li–O2 batteries and determines rate, capacity, and reversibility. Current understanding states that the partition between surface adsorbed and dissolved lithium superoxide governs whether Li2O2 grows as a conformal surface film or larger particles, leading to low or high capacities, respectively. However, better understanding governing factors for Li2O2 packing density and capacity requires structural sensitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 71 publications
3
42
0
Order By: Relevance
“… 16 , 17 , 20 23 In a recent study with operando small- and wide-angle X-ray scattering (SAXS/WAXS), we found that Li 2 O 2 structures indicating surface growth are absent even in weakly LiO 2 -solvating electrolytes and at high overpotentials. 10 This is in line with large Li 2 O 2 particles imaged via electron microscopy in weakly solvating electrolytes at practical current densities and raises questions about the surface mechanism occurring. 24 − 27 Consequently, truly capacity-limiting factors as well as measures and governing factors for Li 2 O 2 packing density are still obscure.…”
supporting
confidence: 57%
See 3 more Smart Citations
“… 16 , 17 , 20 23 In a recent study with operando small- and wide-angle X-ray scattering (SAXS/WAXS), we found that Li 2 O 2 structures indicating surface growth are absent even in weakly LiO 2 -solvating electrolytes and at high overpotentials. 10 This is in line with large Li 2 O 2 particles imaged via electron microscopy in weakly solvating electrolytes at practical current densities and raises questions about the surface mechanism occurring. 24 − 27 Consequently, truly capacity-limiting factors as well as measures and governing factors for Li 2 O 2 packing density are still obscure.…”
supporting
confidence: 57%
“…(ii) LiO 2 is soluble and mobile even in weakly solvating electrolytes ( Figure 2 ). (iii) Li 2 O 2 forms to the widest extent via solution-mediated DISP ( Figure 2 and a recent operando SAXS/WAXS study 10 ). (iv) Li 2 O 2 particles become smaller and more numerous with increasing current ( operando SAXS/WAXS 10 and refs ( 8 ), 14 , ( 36 ), and ( 37 )).…”
Section: A Reconsidered Oxygen Reduction Mechanismmentioning
confidence: 88%
See 2 more Smart Citations
“…Consistent with the above results, a very recent study from Prehal et al reported that higher species mobilities and electrode surface area, namely lower overpotentials, can facilitate the solution-mediated growth of the Li 2 O 2 and a high capacity even in the low DN solvent. 61 Therefore, they proposed a unified ORR mechanism, which includes the dependence of dissociation of solvated LiO 2 , species mobilities and areal current densities.…”
Section: Orr Mechanismmentioning
confidence: 99%